The Application of IoT on Consumer Behaviour and Decision-Making Process - Khazaei, Hamed; Wei, Chng Kok; Sulaiman, Shameer Khan Bin (International Journal of Advanced Science Computing and Engineering, 2022)
The Internet of Things (IoT) is developing as a substantial tool in information technology. It can potentially enhance the efficiency and convenience of human life. This proposal presents a review of recent experimental studies that suggested applications of the Internet of Things (IoT) on consumer behaviour and decision-making processes. The studies have done review research in the domain of the IoT to measure or observe the consumer decision-making process. I believe there are still research gaps in this field. Several studies can present an understanding of the possible applications of IoT in marketing to sense potential consumer purchasing behavior and components of the decision-making process in detail.